Tailored Investments Needed to Support Weather, Water, Ice, and Climate Services in the Polar Regions - Lamers, Machiel; Ljubicic, Gita; Thoman, Rick; Carrasco Cerda, Jorge Fernando; Dawson, Jackie; Heinrich, Victoria J.; Jeuring, Jelmer; Liggett, Daniela; Stewart, Emma J. (My University, 2024)
The Polar Prediction Project (PPP), one of the flagship programs of the World Meteorological Organization's (WMO) World Weather Research Programme (WWRP), has come to an end after a decade of intensive and coordinated international observing, modeling, verification, user engagement, and education activities. While PPP facilitated many advancements in modeling and forecasting, critical investment is now required to turn prediction science into salient environmental services for the polar regions. In this commentary, the members of the Societal and Economic Research and Applications task team of PPP, a group of social scientists and service delivery specialists, identify a number of insights and lessons that are critical for the implementation of the follow-up program Polar Coupled Analysis and Prediction for Services (PCAPS). We argue that in order to raise the societal value of polar environmental services, we need to better understand the diversity of highly specific user contexts; to tailor the actionability of weather, water, ice, and climate (WWIC) service development in the polar regions through inclusive transdisciplinary approaches to coproduction; to assess the societal impact of improved environmental services in the polar regions; and to invest and provide dedicated funding for involving the social sciences in research and tailoring processes across all the polar regions.
Keywords: social science; antarctica; arctic